Demystifying the Relationship Between Students’ L2 Grit and L2 Hope - Guo, Gongwei; Liu, Honggang (Journal of Psychological Perspective, 2025)
Given the affective turn in the second-language (L2) research and the vital roles of L2 grit and L2 hope in learners’ academic achievement, this quantitative study aimed to explore Chinese senior high students’ L2 grit and L2 hope and examine whether there were possible correlations among the two variables and their components. 335 Chinese senior high students completed the questionnaire. Participants reported moderate levels of global L2 grit and L2 hope, but high levels of consistency of interest (COI). Additionally, no statistically significant gender difference could be observed among variables under investigation, while a statistically significant grade-level difference emerged in global L2 grit and global L2 hope, particularly in perseverance of effort (POE) and pathway. Furthermore, global L2 grit positively correlated with global L2 hope with a small-to-medium effect size. Among components of global L2 grit, POE exhibited the strongest association with L2 hope and its components. These findings extend the positive psychology framework in L2 research by highlighting the close link between L2 grit and L2 hope. Practically, the results suggest that English-as-a-foreign-language (EFL) instructors, particularly within the high-intensity examination-oriented educational settings, should spotlight EFL learners’ positive psychological traits in daily teaching practices to promote learners’ well-being during their learning journey.